Mechanisms of Shared Vulnerability to Post-traumatic Stress Disorder and Substance Use Disorders - María-Ríos, Cristina E.; Morrow, Jonathan D. (Frontiers in Behavioral Neuroscience, 2020)
Psychoactive substance use is a nearly universal human behavior, but a significant minority of people who use addictive substances will go on to develop an addictive disorder. Similarly, though ~90% of people experience traumatic events in their lifetime, only ~10% ever develop posttraumatic stress disorder (PTSD). Substance use disorders (SUD) and PTSD are highly comorbid, occurring in the same individual far more often than would be predicted by chance given the respective prevalence of each disorder. Some possible reasons that have been proposed for the relationship between PTSD and SUD are self-medication of anxiety with drugs or alcohol, increased exposure to traumatic events due to activities involved in acquiring illegal substances, or addictive substances altering the brain’s stress response systems to make users more vulnerable to PTSD. Yet another possibility is that some people have an intrinsic vulnerability that predisposes them to both PTSD and SUD. In this review, we integrate clinical and animal data to explore these possible etiological links between SUD and PTSD, with an emphasis on interactions between dopaminergic, adrenocorticotropic, gabaergic, and glutamatergic neurobehavioral mechanisms that underlie different emotional learning styles.